The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1021/ie400886u
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hybrid Scheme for Making Feasible Numerical Investigations of Industrial Three-Phase Flows with Aggregation

Abstract: This Research Note proposes an innovative modeling and computational scheme for investigating industrial threephase flows with aggregation. The scheme is applied on an industrially relevant application: dissolved air flotation. Aggregate formation is modeled locally using a sophisticated subgrid model, and a concept involving massless tracer particles is invoked to transport the aggregate properties, along with the flow. The model is able to account for the formation and consumption of all entities involved an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…A model of such an industrial system must therefore be able to handle all the links in this chain in order to deduce any information about the performance of the equipment. A promising route to such simulations is via so-called hybrid schemes [39]. The method presented in the current work can be used for the derivation of hydrodynamic interaction forces between different configurations of bubbles and particles, as well as bubble-particle attachment probabilities as functions of locally varying parameters.…”
Section: Simulations Of Industrial Unitsmentioning
confidence: 99%
“…A model of such an industrial system must therefore be able to handle all the links in this chain in order to deduce any information about the performance of the equipment. A promising route to such simulations is via so-called hybrid schemes [39]. The method presented in the current work can be used for the derivation of hydrodynamic interaction forces between different configurations of bubbles and particles, as well as bubble-particle attachment probabilities as functions of locally varying parameters.…”
Section: Simulations Of Industrial Unitsmentioning
confidence: 99%
“…Among different turbulence models, K‐ε has the highest application and provides more consistent results with experimental works (Bloom & Heindel, 2003; Deng et al, 2017; Kim et al, 2015; Lakghomi et al, 2015a, 2015b). Also, mathematical models have been used to simulate the particle size and forces acting on it together with the flow conditions in DAF (Bondelind et al, 2013; Dong‐Heui & Mi‐Sug, 2018; Ström et al, 2013). Shahbazi showed that micro‐turbulences have a more significant effect on particle flotation.…”
Section: Introductionmentioning
confidence: 99%